Mapping Keywords in Granny Josie’s Culinary Heritage Using Large Language Models - Karol Król (Heritage)
Culinary heritage is central to preserving cultural identity. The present study analyses the content of culinary notebooks from 1946 and 1947 using large language models (LLMs) and a dedicated AI plugin, Linguistic Insight (LI-AI). The general goal was to analyse content in Granny Josie’s Notebooks (the BaJa corpus) with AI tools. The specific objective was to create and test a dedicated analytical tool, an LI-AI ChatGPT plugin for the in-depth analysis of the BaJa corpus, focusing on ingredients, techniques, and recipes. LI-AI identified keywords and main themes in the large textual dataset. It then visualised them as word clouds. Compared to manual tools, LI-AI’s semantic analysis was more precise and comprehensive. This study contributes to the analysis of historical culinary practices in post-war Poland, revealing that cooking had not only a pragmatic role but also a symbolic one as it supported social and family bonds. This finding was not evident in the word clouds. Instead, it emerged from an in-depth semantic analysis. This study has confirmed the practical value of LLMs in historical text interpretation. It also established that the parallel use of AI and manual tools is advisable for a fuller analysis of textual data.